Discordance, accuracy and reproducibility study of pathologists’ diagnosis of melanoma and melanocytic tumors - Sarah Haggenmüller; Christoph Wies; Julia Abels; Jana T. Winterstein; Lukas Heinlein; Carina Nogueira Garcia; Jochen S. Utikal; Sebastian A. Wohlfeil; Friedegund Meier; Sarah Hobelsberger; Frank F. Gellrich; Mildred Sergon; et al. (Nature Communications)
Abstract Accurate melanoma diagnosis is crucial for patient outcomes and reliability of AI diagnostic tools. We assess interrater variability among eight expert pathologists reviewing histopathological images and clinical metadata of 792 melanoma-suspicious lesions prospectively collected at eight German hospitals. Moreover, we provide access to the largest panel-validated dataset featuring dermoscopic and histopathological images with metadata. Complete agreement is achieved in 53.5% of cases (424/792), and a majority vote ( ≥ five pathologists) in 90.9% (720/792). Considerable discordance is observed for non-invasive melanomas (complete agreement in only 10/73 cases). The expert panel disagrees with the local pathologists’ and dermatologists’ diagnoses in 14.9% and 33.5% of cases, respectively. This variability highlights the diagnostic challenges of early-stage melanomas and the need to reconsider how ground truth is established in routine care and AI research. Including at least two pathologists or virtual panels may contribute to more consistent diagnostic results.